1992
DOI: 10.1007/bf00175924
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia keratoconjunctivitis determination of Chlamydia trachomatis specific secretory immunoglobulin A in tears by enzyme immunoassay

Abstract: Determination of Chlamydia trachomatis specific antibodies in serum and tears, isolation of C. trachomatis in cell culture and C. trachomatis antigen detection by direct immunofluorescence test were evaluated for the laboratory diagnosis of Chlamydia trachomatis infection in 30 patients with chronic conjunctivitis. C. trachomatis specific secretory immunoglobulin A (s-IgA) was detected in the tears of all 8 patients with a positive result in culture and the direct immunofluorescence test. In 4 additional patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Concomitantly elevated serum IgG and IgA level has proved to be a useful marker of suspected chronic C. pneumoniae infection in asthma patients [16], and it was reasonable to assume that this might be true for COPD patients as well. It has been suggested that the presence of short-lived sIgA antibodies in secretion indicates on-going infection in several chlamydia infections even more reliably than serology [24,25]. Furthermore, the PCR technique has proved to be more sensitive than culture in various infections caused by C. trachomatis [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly elevated serum IgG and IgA level has proved to be a useful marker of suspected chronic C. pneumoniae infection in asthma patients [16], and it was reasonable to assume that this might be true for COPD patients as well. It has been suggested that the presence of short-lived sIgA antibodies in secretion indicates on-going infection in several chlamydia infections even more reliably than serology [24,25]. Furthermore, the PCR technique has proved to be more sensitive than culture in various infections caused by C. trachomatis [26][27][28].…”
Section: Discussionmentioning
confidence: 99%